Handbook of Research on E-Learning Methodologies for Language Acquisition 2009
DOI: 10.4018/978-1-59904-994-6.ch021
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Academic Podcasting on Students' Learning Outcomes

Abstract: As part of an initiative to enhance the humanities’ use of emerging technologies, the Department of Foreign Languages and Literatures at Old Dominion University is currently developing strategies for incorporating the use of podcasting—disseminating audio programming over the Internet—in its foreign language curricula and is studying podcasting’s effects on foreign language teaching and learning. The academic use of podcasting allows for 24/7 accessibility and portability of the teaching and learning experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Podcasting changes the study propensities the same number of understudies no longer attempt to take part in conventional classes, yet they like to connect with the course substance for all intents and purposes (Facer, Abdous, & Camarena, 2009;McCombs & Liu, 2007). By executing podcasting to classroom educational programs, a noteworthy feeling of adaptability is improved as understudies will not miss any point in the event that they dropped any session.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Podcasting changes the study propensities the same number of understudies no longer attempt to take part in conventional classes, yet they like to connect with the course substance for all intents and purposes (Facer, Abdous, & Camarena, 2009;McCombs & Liu, 2007). By executing podcasting to classroom educational programs, a noteworthy feeling of adaptability is improved as understudies will not miss any point in the event that they dropped any session.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…In a number of research studies, podcasts were found to make a positive effect on students' attitudes (e.g., Abdous et al, 2009;Alshaikhi & Madini, 2016;Lu, 2007), and they were thought to improve listening comprehension (Alm, 2013;Ashraf, Noroozi, andSalami, 2011 as cited in Al Fadda &Al Qasim, 2013;Giordano, 2016;Li, 2010). In some other studies, podcasts were found to improve students' study practices (Facer et al, 2008). As they can be used anytime/anywhere and students have control over what to listen to, podcasts could be valuable materials for extensive listening and useful tools for personal and professional development.…”
Section: Benefits Of Podcastsmentioning
confidence: 99%
“…As they can be used anytime/anywhere and students have control over what to listen to, podcasts could be valuable materials for extensive listening and useful tools for personal and professional development. A particular benefit of podcasts is that they expose language learners to authentic language through the materials of their own choice (Al Fadda & Al Qasim, 2013;Alm, 2013;Bittenbender & Von Koss, 2008;Facer et al, 2008;Farangi et al, 2015;Hasan & Hoon, 2013;Jain & Hashmi, 2013). This is particularly important in input-poor contexts, in which students have limited opportunity to listen to language in authentic contexts.…”
Section: Benefits Of Podcastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las aplicaciones del podcasting (weblogs audio, archivos sonoros y grabadoras web) en la enseñanza de lenguas han sido abordadas por diferentes autores y revisiones bibliográficas (Lomicka y Lord, 2011;Burston, 2013;Hasan y Hoon, 2013). Muchos trabajos han puesto de relieve la importancia del podcasting para la adquisición de competencias lingüísticas como la gramática (Istanto, 2011), el vocabulario (Borgia, 2010;Putman y Kingsley, 2012), así como para el incremento de la comprensión oral (Lee y Chan, 2007;Schmidt, 2008;Facer et al, 2009;Knight, 2010;Shiri, 2015). Algunos estudios se han centrado en el desarrollo de la producción oral o en la enseñanza de la pronunciación (McQuillan, 2006;Travis y Joseph, 2009;Lord, 2008;Ducate y Lomicka, 2009;Tomé, 2009Tomé, , 2011Fitria et al, 2015).…”
Section: Antecedentesunclassified